ZnO Growth on PMMA-Coated Glass by Solution-Immersion Method: Influence of Immersion Time towards the Optical Properties of ZnO - Aadila, A.; Afaah, A. N.; Asib, N. A. M.; Mohamed, R.; Rusop, M.; Khusaimi, Z. (New Approaches in Engineering Research Vol. 5, 2021)
ZnO growth on PMMA-coated substrate under influence of different immersion time by solution-immersion technique was investigated. PMMA polymer was coated on a glass substrate by spin-coating method. The PMMA-coated substrate was then prepared for non-immersed and immersed for four (4) and six (6) hours in zinc solution. The optical properties of the film obtained were characterized using Photoluminescence (PL), Raman Spectra and Ultraviolet-Vis (UV-Vis) spectroscopy. It was found that shorter time of immersion (4 hours) produced higher intensity of PL and Raman. However, the reverse was found for UV-Vis measurement. The low absorption that was shown from the film immersed for 4 hours may correspond to the random distribution and orientation of ZnOparticle growth on PMMA-coated substrate.